2020
DOI: 10.1017/s1355617720001204
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition and Cognitive Decline in Patients with Parkinson’s Disease

Abstract: Social cognition (SC) comprises an array of cognitive and affective abilities such as social perception, theory of mind, empathy, and social behavior. Previous studies have suggested the existence of deficits in several SC abilities in Parkinson disease (PD), although not unanimously. Objective: The aim of this study is to assess the SC construct and to explore its relationship with cognitive state in PD patients. Method: We compare 19 PD patients with cognitive decline, 27 cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 78 publications
(105 reference statements)
4
28
1
Order By: Relevance
“…A relationship between affective ToM and visuospatial function was also shown, arguing that the second could explain the first even in early stages of PD [69]. Later, Alonso-Recio et al, [14] found an association between affective ToM (measured with RMET) and processing speed, memory, and EF.…”
Section: Relationship With Other Cognitive Functions and General Cognitive Functionmentioning
confidence: 88%
See 3 more Smart Citations
“…A relationship between affective ToM and visuospatial function was also shown, arguing that the second could explain the first even in early stages of PD [69]. Later, Alonso-Recio et al, [14] found an association between affective ToM (measured with RMET) and processing speed, memory, and EF.…”
Section: Relationship With Other Cognitive Functions and General Cognitive Functionmentioning
confidence: 88%
“…A wide variety of tools have been used to evaluate ToM in PD [12,14,52]. Some of the tests have shown good reliability and sensitivity in other neurodegenerative disorders such as the behavioral variant of frontotemporal dementia (bvFTD) [15].…”
Section: Clinical Assessment Of Tom In Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, previous research proposed that dorso-lateral prefrontal areas and nigrostriatal dopaminergic circuits damage results in cognitive decline, such as, inferencing mental states of other people. Likewise, damage to ventromedial, orbitofrontal prefrontal cortex and mesolimbic circuits could result in inability to infer emotional states in others (Alonso-Recio et al, 2020;Bodden, Dodel, & Kalbe, 2010;Koirala et al, 2019;Luo et al, 2014). Social-pragmatic abilities entail the capability of people to communicate in different contexts, as well as recognize and express communicative intentions (Bara, 2010, Coundouris et al, 2019.…”
Section: Introductionmentioning
confidence: 99%